Daoist political ecology as green party ideology: The case of the Swedish greens - JOSHI, Devin K. (Institutional Knowledge at Singapore Management University, 2022)
Green parties were once hailed as offering a “new politics” vis-à-vis the political establishment by proposing radical political, economic, and environmental reforms, but they have since transformed in many countries to become more moderate and pragmatic. While some doubt whether their ideology still contains any essential core, I contend that a unifying link can be found in the philosophy of the Daoist sage Laozi. I illustrate this by analyzing the party program of Miljöpartiet de Gröna (Sweden's Environmental Green Party), one of the world's most electorally successful green parties. As demonstrated here, this green party's current ideology strongly reflects key imperatives of Daoist political ecology revealing the philosophy's durability and attractiveness over time and its perceived relevance to pressing issues of sustainability and climate change.